The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1139/m74-157
|View full text |Cite
|
Sign up to set email alerts
|

Action of light on Micrococcus roseus

Abstract: 1974. Action of light on Micrococc~ts roseus. Can. J.Microbiol. 20: 1015-1021. Micrococc~ts roseus is killed by exposure to a continuous spectrum of white light (3000 ft-c (32 292 Im/m2)) in the presence of air and the dye, toluidine blue. Comparison of rates of photodynamic killing for log and stationary phase cells and for two pigmentation mutants indicated that photosensitivity could not be correlated with amount of carotenoid or with carotenoid-chromophore length. Moreover, cells grown in medium containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

1977
1977
1992
1992

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
(9 reference statements)
0
6
2
Order By: Relevance
“…Procedures similar to those used here were used to demonstrate repair of photodynamic damage in Escherichia coli (Das et al, 1974). However, we were not able to substantiate the suggestion of Schwartzel and Cooney (1974b) that M . roseus has a repair mechanism.…”
Section: Resultscontrasting
confidence: 94%
See 3 more Smart Citations
“…Procedures similar to those used here were used to demonstrate repair of photodynamic damage in Escherichia coli (Das et al, 1974). However, we were not able to substantiate the suggestion of Schwartzel and Cooney (1974b) that M . roseus has a repair mechanism.…”
Section: Resultscontrasting
confidence: 94%
“…The absorption spectrum of pigments from the wild type (Fig. 2) are typical of a mixture of canthaxanthin, echinenone, 4-hydroxyechinenone, and other pigments with a /I-carotene chromophore previously identified (Cooney et a!., 1966;Schwartzel and Cooney, 1970, 1972, 1974b. Two mutants, labeled W H and 10.5, respectively, appear to lack colored carotenoids.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Cooney et al (165), Ungers and Cooney (826), and Schwartzel and Cooney (710) reported canthaxanthin to be the major pigment in Micrococcus roseus. Canthaxanthin has its widest distribution in marine organisms.…”
Section: Canthaxanthin For Yolk Pigmentationmentioning
confidence: 99%